2013
DOI: 10.1007/s11064-013-1224-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Potential Antidepressant-Like Activity of Chalcone-1203 in Various Murine Experimental Depressant Models

Abstract: Two classic animal behavior despair tests-the forced swimming test (FST) and the tail suspension test (TST) were used to evaluate antidepressant-like activity of a new chalcone compound, chalcone-1203 in mice. It was observed that chalcone-1203 at dose of 1, 5, and 10 mg/kg significantly reduced the immobility time in the FST and TST in mice 30 min after treatment. In addition, chalcone-1203 was found to exhibit significant oral activity in the FST in mice. It also produced a reduction in the ambulation in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Chalcone-1203 significantly increased the concentrations of 5-HT and NE in the hippocampus, hypothalamus and cortex and significantly lowered the ratio of 5-HIAA/5-HT in the hippocampus and cortex, slowing down 5-HT metabolism compared with stressed mice treated with vehicle. The mechanism of action of chalcone-1203 may be because of increased 5-HT and NE in the mouse hippocampus and cortex [102].…”
Section: Chalcone and Flavanone Compoundsmentioning
confidence: 99%
“…Chalcone-1203 significantly increased the concentrations of 5-HT and NE in the hippocampus, hypothalamus and cortex and significantly lowered the ratio of 5-HIAA/5-HT in the hippocampus and cortex, slowing down 5-HT metabolism compared with stressed mice treated with vehicle. The mechanism of action of chalcone-1203 may be because of increased 5-HT and NE in the mouse hippocampus and cortex [102].…”
Section: Chalcone and Flavanone Compoundsmentioning
confidence: 99%
“…Briefly, naive mice received a single injection of vehicle/fluoxetine (20 mg/kg)/Andro (10, 20, 50, or 100 mg/kg). After 30 minutes, the FST, TST, or OFT was performed (Farzin and Mansouri, 2006; Wang et al, 2008; Guan et al, 2014). Separate groups of mice were used for the 3 tests (n = 10).…”
Section: Methodsmentioning
confidence: 99%
“…Supported by the above results, in this work, we designed and synthesised some novel H 3 R antagonists/inverse agonists by hybriding the H 3 R pharmacophore (aliphatic amine with propyloxy chain) with the 1,2,4-triazole, the latter have been identified as an important and effective anticonvulsive fragment in recent years (Figure 1, II and III) [33][34][35][36][37] . According to Quan's reports, the 1,2,4-triazole derivatives were likely to have several mechanisms of action such as inhibiting voltage-gated sodium ions channel and modulating GABAergic activity [38][39][40] . And a group of Plech illustrated the anticonvulsive effects of 4-alkyl-5-aryl-1,2,4-triazole-3-thione derivatives and suggested that the influence on the voltage-gated Na þ channels was involved in them at least 41,42 .…”
Section: Introductionmentioning
confidence: 99%